Management of Fracture-Related Infection in Conflict Zones: Lessons Learned from Medical Missions to Gaza - Elias Nasser; Nour Alshaer; Muaaz Wajahath; Bilal Irfan; Mohammed Tahir; Mosab Nasser; Khaled J. Saleh (Antibiotics)
Background/Objectives: Fracture-related infections (FRIs) are a significant complication in conflict zones, where limited resources and damaged infrastructure complicate orthopedic care. Methods: This study retrospectively reviews the management of FRIs during medical missions to Gaza from April to July 2024. Results: Among 135 patients treated for war-related fractures, 30% were identified with suspected FRIs, which were primarily following explosive injuries. Contributing factors to the high incidence of infection included malnutrition, poor sanitation, and the scarcity of sterile surgical supplies. The absence of standard infection control measures further complicated treatment. Conclusions: These findings highlight the critical need for a comprehensive approach that incorporates infection prevention, sustainable healthcare planning, and quality assurance tailored to the realities of conflict zones. The study underscores the importance of international support to ensure the availability of essential medical supplies and to develop effective, context-specific strategies for infection management. By applying these insights, healthcare providers can improve patient outcomes and reduce the burden of FRIs in resource-limited settings affected by conflict.